ERGONOMIC STUDY OF RIDE-HAILING APPLICATION INTERFACE DESIGN BASED ON BIOMECHANICS ANALYSIS OF FINGER MUSCLES (CASE STUDY: GOJEK AND GRAB APPLICATIONS) - Karunia Kusumah, Gina
The development of internet technology and smartphones that can be carried anywhere provides opportunities for application-based ride-hailing businesses such as Gojek and Grab. In the ride-hailing service business, the application is the most important product to run the business. The context of use is important because the use of ride-hailing applications occurs at a time when users tend to be in a condition with high mobility. At that moment, users have a tendency to use the cellphone with one hand which means that the control of the cellphone is controlled by the thumb. Some studies state that the use of mobile phones like this can cause finger and hand muscle fatigue. However, not many studies have looked at the electrical activity of users' finger muscles when ordering ride-hailing services. Therefore, this study observes and compares finger muscle activity when using the Gojek and Grab ride-hailing applications via a mobile phone screen. This research used an electromyography (EMG) instrument along with a recording of touch interactions at the interface. The research method was carried out using a quantitative approach, namely the Wilcoxon Signed Ranks non-parametric statistical test to analyze differences in finger muscle activation when using the Grab and Gojek applications. Touch interaction efficiency is analyzed through mapping the intensity of user touch interactions when using the Gojek and Grab applications to order ride-hailing services using a touch screen by implementing a 4x6 grid. Overall, the results showed that there was no significant difference between muscle activation in the use of the Gojek and Grab applications. However, the Grab app interface is predicted to have less potential for causing muscle fatigue than the Gojek app interface. It is hoped that the findings from this study can be useful as a reference for interface design guidelines for ride-hailing applications.